Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1111/j.1574-695x.2001.tb00526.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the composition of intestinal microflora as a prospective treatment target in infant allergic disease

Abstract: We assessed the fecal microflora of 10 healthy infants and 27 infants with atopic eczema during breast-feeding and after weaning. The atopic infants had less frequently Gram-positive species among the most predominant aerobes and smaller total cell counts. Further differences were associated with more extensive manifestations, seen as higher bacteroides and lower bifidobacteria counts. Weaning resulted in decreased bacteroides counts in atopic and total cell counts in healthy infants and diminished predominanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(76 citation statements)
references
References 47 publications
4
69
0
3
Order By: Relevance
“…Various results of the diversity in the Lactobacillus and Bifidobacterium groups in the allergy patients have been reported; on the one hand, the prevalence of colonic Bifidobacteria was lower in allergic infants than in healthy infants (10,28,35). In addition, Thompson-Chagoyan et al (4) found no differences between children with CMPA and healthy children in terms of the prevalence of the Bifidobacterium and Lactobacillus groups in gut flora.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Various results of the diversity in the Lactobacillus and Bifidobacterium groups in the allergy patients have been reported; on the one hand, the prevalence of colonic Bifidobacteria was lower in allergic infants than in healthy infants (10,28,35). In addition, Thompson-Chagoyan et al (4) found no differences between children with CMPA and healthy children in terms of the prevalence of the Bifidobacterium and Lactobacillus groups in gut flora.…”
Section: Discussionmentioning
confidence: 95%
“…The fecal microbiota characteristics of children with CMPA < 5 years old has been determined; (28) however, studies on the biodiversity of fecal microbiota in children with CMPA > 5 five years old are limited. Importantly, CMPA becomes serious when it affects older children (6, 7).…”
Section: Discussionmentioning
confidence: 99%
“…The resected mucosal biopsies (area = 0.785 cm 2 ) from the distal colon of patients were cut into small pieces, resuspended in 1.4 mL of buffer ASL (QIAamp DNA stool Mini kit, Qiagen, Hilden, Germany), vortexed thoroughly and used for the DNA extraction by using the QIAamp DNA stool Mini kit following the manufacturer's instructions for gram-positive bacteria. DNA extracts were stored at -20℃ until its use.…”
Section: Dna Extractionmentioning
confidence: 99%
“…This intestinal microbiota provides the most important contact with the environment for the host and a barrier against harmful food components and pathogenic bacteria [1,2] . The microbiota has also been shown to have a direct impact on the morphology of the gut [3] and it plays an important role in the intestinal immuno-physiological regulation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the findings of one study are discordant (Sepp et al, 2005) with none of the 5-year-old children with atopic dermatitis and only one child with bronchial asthma colonized with bifidobacteria. Besides, low levels of bifidobacterial colonization have been observed in infants suffering from atopic dermatitis (Kirjavainen et al, 2001;Watanabe et al, 2003;Mah et al, 2006) and in infants suffering from atopic dermatitis and wheezing; note that these results have been contradicted by studies comparing healthy subjects with wheezing infants without other symptoms (Murray et al, 2005) and with patients suffering from both atopic dermatitis and food allergy (Penders et al, 2006a).…”
Section: Microbiota and Allergymentioning
confidence: 54%